Measurement-Induced Nonlocality in an n-Partite Quantum State - Hassan, Ali Saif M.; Joag, Pramod S. (Journal of Amran University, 2021)
We generalize the concept of measurement-induced non-locality (MIN) to an n-partite quantum state. We get exact analytical expressions for MIN in an n-partite pure and n-qubit mixed state. We obtain the conditions under which MiN equals geometric quantum discord in an n-partite pure state and an n-qubit mixed state.